CD8 T-cell Recruitment Into the Central Nervous System of Cuprizone-Fed Mice: Relevance to Modeling the Etiology of Multiple Sclerosis - Almuslehi, Mohammed S. M.; Sen, Monokesh K.; Shortland, Peter J.; Mahns, David A.; Coorssen, Jens R. (Frontiers in Cellular Neuroscience, 2020)
Cuprizone (CPZ)-feeding in mice induces atrophy of peripheral immune organs (thymus and spleen) and suppresses T-cell levels, thereby limiting its use as a model for studying the effects of the immune system in demyelinating diseases such as Multiple Sclerosis (MS). To investigate whether castration (Cx) can protect the peripheral immune organs from CPZ-induced atrophy and enable T-cell recruitment into the central nervous system (CNS) following breach of the blood brain barrier (BBB), three related studies were carried out. In Study 1, Cx prevented the dose-dependent reductions (0.1% < 0.2% CPZ) in thymic and splenic weight, size of thymic medulla and splenic white pulp, and CD4 and CD8 (CD4/8) levels remained comparable to gonadally intact (Gi) control males. Importantly, 0.1% and 0.2% CPZ were equipotent at inducing central demyelination and glial activation. In Study 2, combining Cx with 0.1% CPZ-feeding and BBB disruption with pertussis toxin (PT) enhanced CD8+ T-cell recruitment into the CNS. The increased CD8+ T-cell numbers observed in the parenchyma of the cerebrum, cerebellum, brainstem and spinal cord were confirmed by western blot and flow cytometry analysis of CNS homogenates. In Study 3, PT+0.1% CPZ-feeding to Gi female mice resulted in similar effects on the peripheral immune organs, CNS demyelination and gliosis comparable to Gi males, indicating that testosterone levels alone were not responsible for the immune response seen in Study 2. The combination of Cx+0.1% CPZ-feeding+PT indicates that CPZ-induced demyelination can trigger an ‘inside-out’ immune response when the peripheral immune system is spared, and may provide a better model to study the initiating events in demyelinating conditions such as MS. Key words: castration, gonadally intact, demyelination, gliosis, inside-out, peripheral immune organs, atrophy.